REVIEW OF JURIDIS POLLUTING GOOD NAME THROUGH INTERNET MEDIA - Nila Sutrisna (Universitas Teuku Umar, 2017)
Information technology plays an important role, both in the present and in the future. In thecurrent era of globalization, the highly developed technology is internet technology. Thedevelopment of the internet in Indonesia is very rapidly. However, these developments turned outto also have a negative impact. One of the misuse of the internet is the libel that someone doesagainst the other party Things or circumstances communicated or published through the internetcan be said to be defamatory or defamatory if things or circumstances that are not true for thevictim, whether it is damaging the reputation or that bring material losses for the victims.Publication or communication about the other person may be defamatory or defamatory, whetherdone with explicit words or writings or with a hidden form but containing connotations damagethe reputation of a person or a Company. The Government of Indonesia has established andenacted legal rules governing Information and Electronic Transactions in a form of legislation,namely Law no. 11 of 2008 on Information and Electronic Transactions, as a form of providinglegal protection for victims in criminal defamation. This study aims to examine and know aboutthe form of criminal defamation through the internet media viewed from the perspective of lawand to know the regulatory system against criminal defamation through the internet media interms of legal aspects. This study uses the normative juridical method, which is the approachdone by examining the legislation relevant to the problem under study or looking from thenormative legal aspects. Technique of data collection is done by Research of Library (LibraryResearch), that is by studying book and literature relevant with writing.Keywords: juridical review, defamation, internet media.